A triterpenoid and Steroids from the Twigs of Millettia utilis Dunn. and Their Antioxidant Activities - Ruksilp, Thanatip (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 1 (2020): January - March 2020DO - 10.14456/nujst.2020.5, 2020)
A triterpenoid, betulin together with two steroids, b-sitostenone and pregnenolone were isolated from dichloromethane  crude extract in the twigs of Millettia utilis Dunn. The structures of all isolated compounds were elucidated by basic NMR spectroscopy  and compared with previous literature. All compounds were tested for their antioxidant activities. Betulin revealed moderate activity against ABTS assay. Keywords: Millettia utilis Dunn., steroids, triterpenoid, ABTS, antioxidant activities